Pendampingan Penerapan Sistem Informasi Gampong (SIGAP) untuk Meningkatkan Efisiensi Administrasi dan Layanan Publik di Desa Paya Awe Aceh Tamiang - Zulkifli, Zulkifli; Fajri, Riyadhul; Pahlevi, Reza; izky, Alfaroel; Vianaza, Vianaza; Ulfa M. , Mahdalena; Amanda, Putri (Aceh Journal of Community Engagement (AJCE), 2025)
The application of information technology in village administration management is one of the strategic steps to improve the efficiency and transparency of public services. The Village Information System (SIGAP) is a technology-based solution designed to optimize the management of village administration data, including population data, social activities, finances, and permits. The community service activities of lecturers and students are aimed at assisting village office officials and operators in implementing SIGAP in improving the efficiency of administration and public services in the village. With discussion, demonstration and enlightenment methods. So that SIGAP users in the village demonstrate their abilities and understand the use and benefits of the SIGAP application and can reduce the time required for the administration process, improve data accuracy, and facilitate access to information for the community.